High-strength premixed pervious concrete for surface layer and preparation method of high-strength premixed pervious concrete

By adjusting the composition and proportion of permeable concrete and using common and low-cost materials, the problem of difficult to take into account both the fluidity and strength of permeable concrete during premixing is solved, high strength and good construction results are achieved, and the materials are improved stability and durability.

CN119462003APending Publication Date: 2025-02-18XIYUEFA INT ENVIRONMENTAL PROTECTION NEW MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411549977.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

It is difficult for existing permeable concrete to maintain fluidity and strength at the same time during premixing, and the construction performance is prone to decline during transportation, resulting in poor material quality stability.

Method used

By adjusting the composition and proportion of concrete, the composition of the slurry is designed and adjusted using common and low-cost materials, including cement, double-stage gravel, soluble sulfates, composite water reducing agents and viscosity regulators, etc. It can achieve high strength and good construction results under premixed conditions.

Benefits of technology

The high strength and good construction effect of permeable concrete under premixed conditions are achieved, the water consumption of the system is reduced, the density of the slurry is increased, and the overall strength and durability of permeable concrete are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005114811700000051
    Figure BDA0005114811700000051
  • Figure BDA0005114811700000061
    Figure BDA0005114811700000061
  • Figure BDA0005114811700000081
    Figure BDA0005114811700000081
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and particularly discloses high-strength premixed pervious concrete for a surface layer and a preparation method of the high-strength premixed pervious concrete. The invention relates to high-strength premixed pervious concrete for a surface layer. The concrete comprises the following components in parts by weight: 220 to 300 parts of cement, 1570 to 1720 parts of double-graded broken stone, 85 to 120 parts of water, 50 to 100 parts of mineral powder, 18 to 35 parts of anhydrite, 4 to 10 parts of soluble sulfate, 0 to 50 parts of silica fume, 0 to 50 parts of fly ash of 1000 meshes, 20 to 35 parts of quartz stone fine sand of 80 to 120 meshes, 1 to 2.5 parts of a composite water reducing agent, 0.4 to 2.4 parts of a viscosity modifier, 6 to 10 parts of wollastonite fiber powder and 0.4 to 1 part of a defoaming agent. The composite water reducing agent comprises an ether polycarboxylic acid water reducing agent and an ester polycarboxylic acid water reducing agent. The composition and proportion of the concrete are designed and adjusted, so that the concrete has a good construction effect under the premixing condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of building materials, and in particular to a high-strength premixed permeable concrete for a surface layer and a preparation method thereof. Background Art

[0002] Pervious concrete is an eco-friendly material that contains a large number of interconnected pores, so it has the functional characteristics of water permeability, air permeability, sound absorption and noise reduction. It is mainly used for light-load road paving such as urban greenways, landscape roads, pedestrian auxiliary roads, non-motorized vehicle lanes, squares and ecological parking lots, and can effectively play the role of water seepage, water storage and drainage. Pervious concrete is usually made of slurry wrapped with aggregate particles, and the slurry is made of cementitious materials, additives and water. Due to the large number of macroscopic voids inside pervious concrete, its workability, mechanical properties and durability are significantly different and insufficient compared to ordinary concrete.

[0003] At present, most of the permeable concrete construction in China is carried out by on-site mixing, which has the following shortcomings: (1) A large area is required to stack materials and production tools on site, and it is necessary to coordinate the site, personnel, water and electricity resources, which is difficult to manage; (2) The on-site mixing workload is large, and dust and noise pollution are serious, which does not meet the national requirements for energy conservation, emission reduction, high efficiency and green environmental protection in urban development and construction; (3) The production and construction site conditions are complicated, the management and control conditions cannot be effectively guaranteed, and the material quality stability is poor. Therefore, actively developing premixed permeable concrete is an inevitable trend in the development of permeable concrete production and construction technology. The technical difficulties that currently hinder the premixing of permeable concrete are: the premixed permeable concrete needs to have a certain fluidity to meet the requirements of tank truck loading and unloading, and due to the influence of the transportation radius, this state needs to remain unchanged or change very little for a long time, usually not less than 2 hours; in addition, the concrete cannot sink due to excessive fluidity, thereby blocking the pores and affecting the permeability effect.

[0004] In cement-based concrete systems, water reducers provide dispersion and suspension functions, making concrete have excellent water reduction and construction performance. However, cementitious materials, especially cement, will undergo a series of reactions such as dissolution, crystallization, and precipitation when they come into contact with water. These reactions, on the one hand, reduce the water content in the system and cause changes in the slurry consistency. On the other hand, they cause the polycarboxylic acid side chains in the water reducer to be embedded and fail, destroying the overall dispersion and suspension effect in the system, and the construction performance of permeable concrete deteriorates. For this reason, most optimization practices are to add retarders to concrete for retarding, especially organic retarders with obvious retarding effects, such as molasses, sodium gluconate, tartaric acid, citric acid and its salts, etc. However, adding retarders can only prolong the setting time of concrete, and cannot solve the problem of maintaining the decline in construction performance of permeable concrete within 2 hours, and will bring the hidden danger of reduced strength in the later period.

[0005] In order to improve the strength of permeable concrete, some technical solutions adopt the method of increasing the strength grade of cement, such as using P·O52.5 cement, P·Ⅰ62.5R cement, etc.; some technical solutions add early strength agents to improve the strength, but the addition of early strength agents will affect the working performance of permeable concrete, making it impossible to achieve premixing; and some technical solutions increase the strength by adding some special materials, such as adding resin, graphene oxide, nano-titanium dioxide and other expensive materials, which significantly increases the production cost.

[0006] In summary, although the current permeable concrete has made significant progress in premixing and high reinforcement, it is difficult to take both into account at the same time. Even if both can be taken into account, some expensive special materials need to be used. Therefore, the development of a low-cost, high-strength premixed cement concrete that is easy to obtain and simple to use is of great significance to promoting the construction of sponge cities and the development of the permeable concrete industry. Summary of the invention

[0007] In order to solve the deficiencies in the prior art, the present application provides a high-strength premixed permeable concrete for a surface layer and a preparation method thereof. In the present application, relatively common and low-cost materials are used to prepare permeable concrete, and the composition and proportion of the concrete are designed and adjusted so that it can have higher strength under premixed conditions and have a good construction effect.

[0008] In the first aspect, the present application provides a high-strength premixed permeable concrete for a surface layer, which adopts the following technical solution: A high-strength premixed permeable concrete for a surface layer comprises the following components in parts by weight: 220-300 parts of cement, 1570-1720 parts of double-graded crushed stone, 85-120 parts of water, 50-100 parts of mineral powder, 18-35 parts of anhydrous gypsum, 4-10 parts of soluble sulfate, 0-50 parts of silica fume, 0-50 parts of 1000-mesh fly ash, 20-35 parts of 80-120-mesh quartz fine sand, 1-2.5 parts of composite water reducing agent, 0.4-2.4 parts of viscosity regulator, 6-10 parts of wollastonite fiber powder and 0.4-1 parts of defoaming agent.

[0009] The anhydrous gypsum is natural anhydrous gypsum.

[0010] The easily soluble sulfate is at least one of industrial grade magnesium sulfate heptahydrate and zinc sulfate heptahydrate.

[0011] The composite water reducer is a mixture of an ether polycarboxylic acid water reducer and a slow-release water reducer.

[0012] The water reduction rate of the ether polycarboxylic acid water-reducing agent is not less than 25%.

[0013] Preferably, the slow-release water-reducing agent is an ester polycarboxylic acid water-reducing agent, which has a gradient slow-release function. Its mechanism of action is to gradually hydrolyze and release carboxylate ions with a dispersing effect in an alkaline environment, thereby achieving the effect of slowly dispersing cement particles. The slow-release water-reducing agent of the present invention starts to exert its slow-release function no earlier than 15 minutes after adding water and mixing, and reaches the maximum water-reducing effect no later than 1.5 hours after adding water and mixing.

[0014] Preferably, the mass ratio of the ether polycarboxylate water-reducing agent to the ester polycarboxylate water-reducing agent is (1-1.25):(1-1.25).

[0015] Further adjusting the mass ratio of ether polycarboxylate water-reducing agent to ester polycarboxylate water-reducing agent can help adjust the initial fluidity of permeable concrete and improve the sustainability of dispersion and suspension, thereby achieving premixing of permeable concrete.

[0016] In some preferred embodiments, the mass ratio of the ether polycarboxylate water-reducing agent to the ester polycarboxylate water-reducing agent can be 1:1.25, 1:1 or 1.25:1, etc.

[0017] Preferably, the viscosity modifier includes magnesium aluminum silicate, hydroxypropyl methylcellulose and Wenlun gum.

[0018] By adopting the above technical scheme, under the condition of using a composite water reducer, the applicant found after a large number of raw material selections and attempts that adding magnesium aluminum silicate, hydroxypropyl methylcellulose and Wenlun glue together as viscosity regulators can achieve a thixotropic and water-retaining thickening effect, so that the permeable concrete can maintain good fluidity for a long time under the tank stirring state while avoiding leakage and clogging of the concrete when it is stationary, ensuring that the permeable concrete has a good construction effect under premixed conditions.

[0019] Based on the above technical scheme, the present application designs and adjusts the slurry for wrapping aggregates. First, cement begins to hydrate when it meets water. At this time, the soluble sulfate can quickly provide a large amount of sulfate ions, accelerate the reaction of C3A to form calcium sulfonite, and avoid the change of slurry consistency caused by early hydration reaction of cementitious materials during concrete transportation; second, silica fume and 1000 mesh fly ash are filled between cement particles as ultrafine powders. A large number of fine particles carry charges and repel each other, making cement particles easy to disperse and suspend, which helps to build a reliable and stable dispersed suspension architecture system; third, ether polycarboxylic acid water reducer and ester polycarboxylic acid water reducer are used for composite design, among which ether polycarboxylic acid water reducer is a common water reducer, and ester polycarboxylic acid water reducer is a slow-release water reducer with a gradient slow-release function. The two are used together to form a continuous relay dispersion suspension effect, offsetting the problem of construction performance degradation caused by cement hydration reaction. Through the above three approaches, a slurry with good fluidity and long-term stable suspension can be obtained, which provides the possibility for premixing of permeable concrete. On this basis, magnesium aluminum silicate, hydroxypropyl methylcellulose and Wenlun glue are added together as viscosity regulators to adjust the viscosity of the permeable concrete. The three are combined to enhance the synergy and play a role in thixotropy and water retention and thickening, so that the permeable concrete in the canned stirring state can maintain good fluidity for a long time while having a suitable consistency, avoiding leakage and clogging of holes when the concrete is left stationary, and ensuring the construction effect of the permeable concrete under premixed conditions.

[0020] Pervious concrete is formed by crushed stone wrapped in a slurry layer. The cement hydration process is accompanied by volume shrinkage, and mineral powder and anhydrous gypsum will further react with cement mineral components and hydration products in the later stage of concrete construction. The process of generating calcium sulfonate is accompanied by a certain volume expansion, which can offset part of the shrinkage caused by cement hydration and reduce the possibility of shrinkage and cracking of the slurry layer causing the pervious concrete to fall off or crack and peel off. At the same time, adding a small amount of quartz fine sand to the slurry layer will not cause pore blockage, but also play a role in stabilizing the volume, reduce the possibility of shrinkage and cracking of the slurry layer, and improve the long-term stability and durability of pervious concrete.

[0021] In addition to enabling the permeable concrete to obtain good premix performance, the present application also reduces the water consumption of the system and increases the density of the hardened slurry due to the filling effect of the ultrafine powder and the water-reducing effect of the composite water-reducing agent, thereby enabling the permeable concrete to obtain a hard and dense encapsulation layer, improving the strength while also hindering the intrusion of destructive liquids such as water, salt solutions and other harmful media.

[0022] Preferably, the double-graded crushed stone comprises crushed stones of two groups of particle size ranges, and the particle sizes of the crushed stones of the two groups of particle size ranges are selected from any two groups of 3-5 mm, 4-6 mm and 5-10 mm.

[0023] By adopting the above technical solution and selecting any two groups of crushed stones within the above particle size range, the macropores can be reduced, the pore structure can be optimized, and the structural stability and mechanical indicators of the permeable concrete can be improved while ensuring the total porosity.

[0024] Preferably, in the double-graded crushed stone, the volume proportion of crushed stone in a large particle size range is not less than 60%.

[0025] Preferably, the curing method of the permeable concrete is as follows: after the permeable concrete hardens, spray 2wt%-4wt% sodium carbonate aqueous solution on the surface of the permeable concrete.

[0026] By adopting the above technical scheme, calcium hydroxide in the cement hydration product is a soluble harmful product. Carbonation treatment of it can promote its further transformation, thereby improving the density and strength of the permeable concrete system. However, considering the requirements of premixing, carbon dioxide, carbonic acid or carbonates cannot be directly added to the concrete system. Therefore, this application chooses to use carbonate solution for curing hardened concrete, which can improve the strength of premixed permeable concrete to a certain extent.

[0027] In a second aspect, the present application provides a method for preparing high-strength premixed permeable concrete for a surface layer, using the following technical solution: A method for preparing high-strength premixed permeable concrete for a surface layer comprises the following steps: adding water into a mixer, then adding cement, mineral powder, anhydrous gypsum, soluble sulfate, silica fume, 1000 mesh fly ash, 80-120 mesh quartz fine sand, composite water reducing agent, viscosity regulator, wollastonite fiber powder and defoamer, stirring at 50-80 rpm for 2-5 minutes, then adding double-graded crushed stone, stirring at 50-80 rpm for 1-3 minutes to obtain permeable concrete.

[0028] By adopting the above technical solution, the components except the double-graded crushed stone are first put into the mixer for stirring, so that the silica fume and 1000 mesh fly ash are filled between the cement particles to form a stable dispersed slurry, and then the double-graded crushed stone is added so that the slurry can evenly wrap the surface of the crushed stone. The operation steps are simple, and it is easy to mass produce, and the produced permeable concrete can have a higher strength under the condition of premixing.

[0029] In summary, the present application includes at least one of the following beneficial technical effects: 1. Realize premixed permeable concrete: The present application uses a variety of methods to make the permeable concrete have good premix performance, such as: adding silica fume and fly ash to fill them between cement particles, so that the cement particles are easy to disperse; the cementitious material is combined with soluble sulfate to accelerate the reaction process of C3A to form calcium sulfate, and avoid the thickening of concrete during early production and transportation; the ether polycarboxylate water reducer and ester polycarboxylate water reducer are compounded to play a continuous dispersing and water-reducing role; magnesium aluminum silicate, hydroxypropyl methylcellulose and Wenlun glue are used to adjust the viscosity of concrete slurry, so that the concrete has good thixotropic and water-retaining effects; 2. Achieve high strengthening of permeable concrete: By adopting the technical solution provided in this application, on the one hand, by using double-graded crushed stone aggregate, the proportion of large pores is reduced while ensuring the total pores, the pore structure is optimized, and the structural stability and mechanical properties of permeable concrete are improved; on the other hand, by optimizing the slurry design, the water consumption of the system is reduced, and the density of the slurry layer wrapping the aggregate is increased, thereby improving the overall strength of the permeable concrete.

[0030] 3. Optimizing the volume stability and durability of permeable concrete: The long-term process of cement hydration is accompanied by large shrinkage, which is particularly obvious in the pure paste. Permeable concrete is a thin pure paste layer wrapped with stones, which is prone to shrinkage and cracking of the wrapping layer, causing defects such as particle shedding or cracking and peeling. The present invention adds mineral powder and anhydrous gypsum, which further react with cement mineral components and hydration products to generate calcium sulfoxide. In the process, a certain volume expansion is accompanied, which can offset part of the shrinkage caused by cement hydration. At the same time, adding a small amount of fine quartz sand to the pure paste will not cause pore blockage, but also play a certain role in stabilizing the volume, reducing the possibility of shrinkage and cracking of the paste. DETAILED DESCRIPTION

[0031] In order to make the present application easier to understand, the present application will be further described in detail below in conjunction with the examples, which are merely illustrative and are not intended to limit the scope of application of the present application. The raw materials or components used in the present application can be obtained through commercial routes or conventional methods unless otherwise specified.

[0032] Embodiment 1-4: The raw material composition of the permeable concrete in Examples 1-4 is shown in Table 1, wherein PO42.5 cement is selected.

[0033] The preparation method of permeable concrete is as follows: first add water into a mixer, then add PO42.5 cement, mineral powder, anhydrous gypsum, soluble sulfate, silica fume, 1000 mesh fly ash, 100 mesh quartz fine sand, composite water reducer, viscosity regulator, wollastonite fiber powder and defoamer, stir at 50-80rpm for 2-5min, then add double-graded crushed stone, stir at 50-80rpm for 1-3min to obtain permeable concrete.

[0034] The curing method of permeable concrete is as follows: after the concrete hardens, spray sufficient water on the concrete surface and cure for 28 days.

[0035] Embodiment 5-7: The raw material composition of the permeable concrete in Examples 5-7 is shown in Table 1, and the preparation method of the permeable concrete is the same as that in Example 1.

[0036] The curing method of permeable concrete is as follows: after the concrete hardens, spray a sufficient amount of 3wt% sodium carbonate aqueous solution on the concrete surface and cure for 28 days.

[0037] Table 1. Raw material dosage of permeable concrete in Examples 1-7 and Comparative Examples 1-2 (kg) Embodiment 8: The difference between Example 8 and Example 4 is that the curing method is different. The curing method of the permeable concrete in Example 8 is as follows: after the concrete is hardened, a sufficient amount of 3 wt % sodium carbonate aqueous solution is sprayed on the concrete surface and cured for 28 days. The rest is the same as Example 4.

[0038] Comparative Example 1: Comparative Example 1 is a representative permeable concrete used for construction by a certain manufacturer, which is only suitable for on-site mixing. The raw material composition of the permeable concrete is shown in Table 1, and the preparation method and curing method of the permeable concrete are the same as those of Example 1.

[0039] Comparative Example 2: The difference between Comparative Example 2 and Example 4 is that crushed stone with a particle size of 5-10 mm is used in equal amounts to replace the double-graded crushed stone, and the rest is the same as Example 4.

[0040] Comparative Example 3: The difference between Comparative Example 3 and Example 4 is that silica fume and fly ash are replaced with cement in equal amounts, and the rest is the same as Example 4. The permeable concrete prepared in Comparative Example 3 began to ooze water within 3 minutes of placement, and then became more serious, with slurry-bone separation and bottom grabbing, which did not meet the requirements for permeable concrete molding.

[0041] Comparative Example 4: The difference between Comparative Example 4 and Example 4 is that an equal amount of ether polycarboxylic acid water-reducing agent is used to replace the composite water-reducing agent, and the rest is the same as Example 4.

[0042] The permeable concrete prepared in Comparative Example 4 had severe initial water seepage and did not meet the requirements for permeable concrete molding. The reason was the same as that in Comparative Example 3.

[0043] Comparative Example 5: The difference between Comparative Example 5 and Example 4 is that an equal amount of a slow-release water reducer is used to replace the composite water reducer, and the rest is the same as Example 4.

[0044] When the permeable concrete was prepared in Comparative Example 5, it was initially relatively dry, the gravel was unevenly wrapped, and it was difficult to shape; although it improved slightly after 15 minutes, it still could not achieve a good shaping effect, did not meet the permeable concrete shaping requirements, and could not meet the premixing requirements.

[0045] Comparative Example 6: The difference between Comparative Example 6 and Example 4 is that the amount of viscosity modifier added is 0, and the rest is the same as Example 4.

[0046] The permeable concrete slurry prepared in Comparative Example 6 has a large fluidity, which will cause the slurry to flow downward and fill the bottom pores during molding, causing the permeable concrete to lose its permeability, and does not meet the permeable concrete molding requirements.

[0047] Comparative Example 7: The difference between Comparative Example 7 and Example 4 is that the dosage of the readily soluble sulfate is 0, and the rest is the same as Example 4.

[0048] The permeable concrete prepared in Comparative Example 7 was in a normal initial state, became slightly thicker within 10 minutes, and then remained stable, which had a slight impact on the molding effect.

[0049] Comparative Example 8: The difference between Comparative Example 8 and Example 4 is that the amount of wollastonite fiber powder added is 0, and the rest is the same as Example 4.

[0050] Test example: Performance tests were conducted on Examples 1-8, Comparative Examples 1-2 and Comparative Examples 7-8, including the holding time, 28d flexural strength, compressive strength, water permeability coefficient and connected porosity, wherein the staff determined the holding time of the permeable concrete by observing the state of the permeable concrete, and the holding time was determined based on the slump loss <20mm and the slurry wrapped around the aggregate remaining full and full. The flexural strength and compressive strength were tested with reference to GB / T 50081 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", and the water permeability coefficient and connected porosity were tested with reference to Appendix A and Appendix B of CJJ / T 135-2009 (2023 Edition) "Technical Specifications for Permeable Cement Concrete Pavement", and the test results are shown in Table 2. Slightly different, the molding time of the test sample was cast according to the holding time measured in Table 2.

[0051] Table 2 It can be seen from the test data in Table 2 that, compared with the permeable concrete prepared in Comparative Examples 1-8, the overall performance of the permeable concrete prepared in Examples 1-8 is better.

[0052] From the test results of Examples 1-7 and Comparative Examples 1-8, it can be seen that the permeable concrete prepared according to the raw materials of the permeable concrete of the present application has better performance than the permeable concrete prepared only from the basic raw materials, indicating that after the slurry that wraps the aggregate is designed and adjusted and the double-graded crushed stone aggregate is matched, the synergistic effect between the components can be fully exerted, so that the permeable concrete can have high strength and excellent stability while achieving premixing. In addition, from the test results of Examples 4 and 8, it can be seen that after the permeable concrete hardens, curing it with an aqueous sodium carbonate solution can improve the compressive strength of the permeable concrete without affecting other properties of the permeable concrete.

[0053] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present invention may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.

Claims

1. A high-strength premixed permeable concrete for surface layer, characterized in that: The permeable concrete comprises the following components by weight: 220-300 parts of cement, 1570-1720 parts of double-graded crushed stone, 85-120 parts of water, 50-100 parts of mineral powder, 18-35 parts of anhydrous gypsum, 4-10 parts of soluble sulfate, 0-50 parts of silica fume, 0-50 parts of 1000 mesh fly ash, 20-35 parts of 80-120 mesh quartz sand, 1-2.5 parts of composite water reducing agent, 0.4-2.4 parts of viscosity regulator, 6-10 parts of wollastonite fiber powder and 0.4-1 parts of defoaming agent; The composite water reducer includes an ether polycarboxylic acid water reducer and a slow-release water reducer.

2. The high-strength premixed permeable concrete for surface layer according to claim 1, characterized in that: The double-graded crushed stone comprises crushed stones of two groups of particle size ranges, and the particle sizes of the crushed stones of the two groups of particle size ranges are selected from any two groups of 3-5 mm, 4-6 mm and 5-10 mm.

3. The high-strength premixed permeable concrete for surface layer according to claim 2, characterized in that: In the double-graded crushed stone, the volume proportion of the crushed stone in the large particle size range is not less than 60%.

4. The high-strength premixed permeable concrete for surface layer according to claim 1, characterized in that: The mass ratio of the ether polycarboxylic acid water reducer to the slow-release water reducer is (1-1.25): (1-1.25).

5. The high-strength premixed permeable concrete for surface layer according to claim 1, characterized in that: The viscosity modifier includes magnesium aluminum silicate, hydroxypropyl methylcellulose and Wenlun gum.

6. The high-strength premixed permeable concrete for surface layer according to claim 1, characterized in that: The easily soluble sulfate is one or both of magnesium sulfate heptahydrate and zinc sulfate heptahydrate.

7. The high-strength premixed permeable concrete for surface layer according to claim 1, characterized in that: The curing method of the permeable concrete is as follows: after the permeable concrete is hardened, a 2wt%-4wt% sodium carbonate aqueous solution is sprayed on the surface of the permeable concrete.

8. A method for preparing permeable concrete according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: adding water into a mixer, then adding cement, mineral powder, anhydrous gypsum, soluble sulfate, silica fume, 1000 mesh fly ash, 80-120 mesh quartz fine sand, composite water reducing agent, viscosity regulator, wollastonite fiber powder and defoamer, stirring at 50-80 rpm for 2-5 minutes, then adding double-graded crushed stone, stirring at 50-80 rpm for 1-3 minutes to obtain permeable concrete.

Citation Information

Cited By

  • Preparation method of Yellow River deposited sand aggregate cement-based water permeable brick

    CN120157419A